Edukasi Pentingnya Pola Hidup Sehat dalam Mencegah Penyakit Tidak Menular - Pomarida Simbolon; Nagoklan Simbolon; Angela Br Surbakti; Angeli Br Surbakti; Selfin Yanti Telaumbanua (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
Non-communicable diseases (NCDs) are a major health problem causing high mortality rates globally, particularly in developing countries, including Indonesia. The main causes of NCDs are closely related to unhealthy lifestyles such as lack of physical activity, poor diet, and smoking. According to WHO data, NCDs account for 74% of all global deaths, with 17 million deaths occurring before the age of 70. In Indonesia, the prevalence of NCDs continues to increase based on the results of the 2013 and 2018 Basic Health Research (Riskesdas). One strategic approach to reducing the risk of NCDs is through health education to encourage behavioral changes towards a healthy lifestyle. This Community Service (PKM) activity aims to increase the knowledge of students of the Health Information Management Study Program at STIKes Santa Elisabeth Medan about the importance of a healthy lifestyle in preventing NCDs. The implementation method included preparation, education using lectures and discussions, and pre- and post-test evaluations. Results showed a significant increase in participants' knowledge after the education. This improvement aligns with several previous studies demonstrating that health education can increase knowledge and encourage the adoption of healthy lifestyle behaviors. Health education has proven effective as an intervention in preventing NCDs among university students. The results showed a difference in average knowledge scores before and after the health education. The conclusion of this health education activity was that the knowledge of MIK students at STIKes Santa Elisabeth Medan increased by 30.87 points. It is hoped that this increased knowledge will lead to changes in student behavior, particularly regarding adopting a healthy lifestyle.